SCUBE1: a promising biomarker in renal cell cancer - Ersagun Karagüzel (International Brazilian Journal of Urology)
ABSTRACT Purpose To investigate the efficacy of signal peptide-CUB-EGF domain-containing protein 1 (SCUBE-1) as a novel biomarker of renal tumors. Materials and Methods 48 individuals were included in the study. The patient group (Group-1) consisted of 23 subjects diagnosed with renal tumor, and the control group (Group-2) of 25 healthy individuals. Patients diagnosed with renal tumor received surgical treatment consisting of radical or partial nephrectomy. Blood specimens were collected following overnight fasting. Signal peptide-CUB-EGF domain-containing protein 1 (SCUBE-1), soluble urokinase plasminogen activator receptor (suPAR) and carbonic anhydrase IX (CA IX) levels were measured from plasma samples. Patients in groups 1 and 2 were compared in terms of these biochemical parameters. Results The 23-member renal tumor group was made up of 17 (73.91%) male and 6 (26.08%) female patients with a mean age of 58.5±15.7 years (range 25 to 80). The 24-member healthy control group was made up of 16 (64%) male and 9 (36%) female subjects with a mean age of 52.4±9.12 years (range 40 to 67). Analysis revealed significant elevation in SCUBE-1 levels in the renal tumor group (p=0.005). No significant differences were detected between the groups with regard to CA IX or suPAR measurements (p=0.062 vs. p=0.176). Conclusions SCUBE-1 appears to represent a promising biomarker in the diagnosis and follow-up of patients with renal tumor.